2020
DOI: 10.3390/jcm9082586
|View full text |Cite
|
Sign up to set email alerts
|

Prior Routine Use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and Important Outcomes in Hospitalised Patients with COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) infection causes acute lung injury, resulting from aggressive inflammation initiated by viral replication. There has been much speculation about the potential role of non-steroidal inflammatory drugs (NSAIDs), which increase the expression of angiotensin-converting enzyme 2 (ACE2), a binding target for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to enter the host cell, which could lead to poorer outcomes in COVID-19 disease. The aim of this study was to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 22 publications
1
48
0
5
Order By: Relevance
“… 40 Although clinical implications of these in vivo findings caused confusion and trepidation in early stages of the COVID-19 pandemic, recent data from patients with COVID-19 show that non-steroidal anti-inflammatory drugs use is not associated with 30-day mortality, hospitalization, intensive care unit admission, mechanical ventilation, or renal replacement therapy in patients with COVID-19. 12 , 50 Similarly, a systematic review found that ACE inhibitors or angiotensin II type-I receptor blockers use was not associated with an increased severity of COVID-19 illness. 51 …”
Section: Sars-cov-2 Neurotropism and Its Implications For Pain Andmentioning
confidence: 99%
“… 40 Although clinical implications of these in vivo findings caused confusion and trepidation in early stages of the COVID-19 pandemic, recent data from patients with COVID-19 show that non-steroidal anti-inflammatory drugs use is not associated with 30-day mortality, hospitalization, intensive care unit admission, mechanical ventilation, or renal replacement therapy in patients with COVID-19. 12 , 50 Similarly, a systematic review found that ACE inhibitors or angiotensin II type-I receptor blockers use was not associated with an increased severity of COVID-19 illness. 51 …”
Section: Sars-cov-2 Neurotropism and Its Implications For Pain Andmentioning
confidence: 99%
“…Several studies are accumulating and reappraising the importance of NSAIDs in COVID-19 management (Bruce et al, 2020;Kutti Sridharan et al, 2020;Smart and Fawkes, 2020;Zolk et al, 2020); interestingly two in silico screenings independently identified the COX-II inhibitor celecoxib as a potential anti-SARS-CoV-2 drug, and a very recent study still under peer review reports its beneficial effects plus famotidine in hospitalized patients (Tomera et al, 2020).…”
Section: Nsaids Paracetamol and Covid-19mentioning
confidence: 99%
“…On the other hand, the warning was immediately questioned ( Moore et al., 2020 ; Rothuizen et al., 2020 ) and few months later a study on the association between routine use of NSAIDs and outcomes in hospitalized COVID-19 patients drawn completely different conclusions ( Bruce et al., 2020 ).…”
Section: Nsaids Paracetamol and Covid-19mentioning
confidence: 99%
“…The bases for that warning mostly relied on anecdotal reports and non-peer-reviewed expert opinions, which went on to speculate that patients may be more vulnerable to SARS-CoV-2 infection if take drugs with proposed ability to increase ACE-2 expression, such as ACE inhibitors, Ang II receptor blockers and ibuprofen [ 57 , 84 ]. Soon after, numerous other global authorities urged prudence and several reports stressed the need for further evidence to get a clearer picture [ 85 , 86 , 87 , 88 , 89 , 90 ]. To this end, four registered trials are currently investigating the impact of ibuprofen (NCT04383899; NCT04334629; NCT04382768) and of naproxen (NCT04325633) on COVID-19 disease.…”
Section: Nsaid Use During Covid-19 Pandemic: Pros and Consmentioning
confidence: 99%
“…In severe cases of COVID-19, ARDS is often associated with the development of a cytokine release syndrome. In this framework, a NSAID-dependent COX inhibition may reduce the recruitment of polymorphonuclear cells (in particular neutrophils) that during the course of inflammation eventually change the profile of lipid mediators produced toward synthesis of SPM metabolites [ 85 , 96 , 99 , 100 , 101 ]. Another potential issue to consider is that the anti-inflammatory and antipyretic effects of NSAIDs and acetaminophen may mask the early symptoms of infection and thus delay diagnosis and rapid management of the affected patients [ 56 , 57 ].…”
Section: Nsaid Use During Covid-19 Pandemic: Pros and Consmentioning
confidence: 99%